A service evaluation of joint working across sectors to promote self-administration of subcutaneous systemic anti-cancer therapy in breast cancer patients. (30th November 2022) - Dodhia, V; Ng, H W; Alves, C; Wojtas, M; Miles, D; Guppy, A; James, S; Harrold, K; Adisa, A; Tome, T; Lyner, Z; Bennett, J; et al.
Abstract: Introduction: Trastuzumab(T) is a humanized monoclonal antibody used in the treatment of HER2-positive breast cancer and is available as a subcutaneous(sc) formulation thereby allowing short and convenient administration. A lack of trained nurses to administer T at home and/or train patients at home to self-administer, together with challenges in maintaining cold-chain delivery have impeded uptake of home administration. 1, 2 In order to support patients' ability to self-administer T at home, we have implemented an educational programme that includes nurse-led training, education material, support apps and follow-up telephone clinics. Home delivery of pre-filled syringes was enabled in collaboration with commercial providers for aseptics and logistic. Aim: The aim of this service evaluation was to evaluate the utility of this programme from the patients' perspective and to assess patient satisfaction and impact on quality of life (QOL). Methods: A previously validated Self-Injection Assessment Questionnaire (SIAQ) 3 was modified to assess patient satisfaction, perceptions and impact of the programme. Patients who had agreed to enrol on the 'self-administration' scheme, were asked to complete the questionnaire at baseline, at the third training session and at the second self-administered dose. Approval from a Research Ethics Committee is not required for this service evaluation. Results: All 14 patients offered the questionnaire responded to all questions. The median age was 58 years old (age range 43-76), 11 patients were Caucasian, 2 were Asian and one was African/Caribbean. The average distance from their home address to hospital was 10.1 miles (range 4-19). Following completion of the one-to-one nurse training there was an improvement in patient confidence to self-administer sc. T. No differences in 'feeling in control of their treatment' or 'satisfaction of attending hospital appointments' were noted. Of the 11 patients who reached the self-administration stage, 10 reported that they felt 'very confident' and 8 reported that it was 'very easy' to give themselves the injection. All patients rated themselves 'very satisfied' with self-administration and reported that the nurse training programme helped them to be more confident. 10 patients reported that the App and written information was useful as well as the pre- and post- administration telephone clinics. All patients reported that the self-administration programme had a positive impact on their QOL by reducing the number of hospital visits. In the first 4 months of self-administration each patient reduced their hospital attendance by an average of 8 appointments (median=8) equating to 10 hours of time that would have been spent at hospital. Discussion/Conclusion: The subcutaneous T self-administration programme was well received by patients. The nurse training sessions and supportive materials enabled patients to feel more confident about self-administration with no reported incidents or adverse events. This led to fewer hospital visits and improved QOL. This programme was critically dependent on the services of a commercial compounder and homecare provider, emphasizing the importance of joint working between the NHS and commercial sector. Evaluation of this programme will continue and will include other agents, including Phesgo ® (sc trastuzumab and pertuzumab) which have more patients and will improve the reliability of the results. References: 1. Tjalma, W., Huizing, M., Papadimitriou, K. The smooth and bumpy road of trastuzumab administration: from intravenous (IV) in a hospital to subcutaneous (SC) at home. Facts Views Vis Obgyn, 2017;9(1):51-55. 2. Grady, PA, Gough, LL. Self-management: a comprehensive approach to management of chronic conditions. American Journal of Public Health 2014; 104(8):e25-31. doi:10.2105/AJPH.2014.302041 3. Keininger D, Coteur G. Assessment of self-injection experience in patients with rheumatoid arthritis: psychometric validation of the Self-Injection Assessment Questionnaire (SIAQ). Health Qual Life Outcomes. 2011;9:2. doi:10.1186/1477-7525-9-2